2007
DOI: 10.1152/ajpregu.00760.2006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypoxia alters NMDA and AMPA-evoked currents in NTS neurons receiving carotid body chemoreceptor inputs

Abstract: Chronic exposure to intermittent hypoxia (CIH) has been used in animals to mimic the arterial hypoxemia that accompanies sleep apnea. Humans with sleep apnea and animals exposed to CIH have elevated blood pressures and augmented sympathetic nervous system responses to acute exposures to hypoxia. To test the hypothesis that exposure to CIH alters neurons within the nucleus of the solitary tract (NTS) that integrate arterial chemoreceptor afferent inputs, we measured whole cell currents induced by activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 46 publications
(50 reference statements)
3
47
0
Order By: Relevance
“…This has been linked to sensitization of the arterial chemoreflex (15,32,45,50,67), which results from a complex mixture of mechanisms ranging from increased O 2 sensitivity of carotid body chemoreceptors (11,21,30,31,50) to enhanced sympathoexcitatory neurotransmission through the brain stem arterial chemoreflex arc (10,18,38,50,67). However, emerging evidence indicates that persistent neurogenic CIH hypertension involves additional adaptive mechanisms that contribute to heightened sympathetic drive.…”
Section: Discussionmentioning
confidence: 99%
“…This has been linked to sensitization of the arterial chemoreflex (15,32,45,50,67), which results from a complex mixture of mechanisms ranging from increased O 2 sensitivity of carotid body chemoreceptors (11,21,30,31,50) to enhanced sympathoexcitatory neurotransmission through the brain stem arterial chemoreflex arc (10,18,38,50,67). However, emerging evidence indicates that persistent neurogenic CIH hypertension involves additional adaptive mechanisms that contribute to heightened sympathetic drive.…”
Section: Discussionmentioning
confidence: 99%
“…Specific 5-HT agonists or antagonists were administered 5 min before paraventricular nucleus injection of NPY, and oxygen consumption, carbon dioxide production, and respiratory quotient were measured 2 h postinjection. Results suggested that 5-HT 2A receptors, within the medial paraventricular nucleus, modulated the action of NPY on food ingestion and energy metabolism (15).…”
Section: Discussionmentioning
confidence: 98%
“…Using immunohistochemistry, we determined that in hamsters' brains 5-HT 2A receptors are located in raphé nucleic, nucleus of the solitary tract (NTS), hypoglossal nuclei, the lateral paragigantocellularus, nucleus, ambiguous nucleus, and ventral tegmental nuclei among others (Schlenker EH and Hansen SN, unpublished observations). These regions, such as the NTS, are important in cardiopulmonary regulation and integration of inputs from carotid body (15). Thus, MDL may have acted on 5-HT 2A receptors in several regions to influence control of breathing.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The latter includes changes in the interaction between sympathetic and respiratory neuronal populations (1,59) and alterations in neurochemical mechanisms in important brain stem areas (30,31). Previous in vitro studies reported that glutamatergic signaling is altered in the NTS of rats submitted to CIH (20,32). In the present study, we confirmed that CIH exposure alters NTS glutamatergic transmission, especially in its caudal aspect-a region that receives the PN frequency (⌬PN, B) and tSN (⌬tSN, C) in response to peripheral chemoreflex activation before (baseline) and 2 min after KYN in the cNTS of control (n ϭ 7) and CIH rats (n ϭ 9).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exogenous microinjections of AMPA evoked higher-amplitude currents in isolated NTS neurons from CIH rats (20), suggesting that glutamatergic signaling is altered in the NTS of rats submitted to CIH. However, these previous studies were performed in vitro, and there is no research on the implication of these glutamatergic changes in the NTS on the control of respiratory and sympathetic activities of CIH rats.…”
mentioning
confidence: 96%